2008
DOI: 10.1016/j.gca.2007.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The age of the martian meteorite Northwest Africa 1195 and the differentiation history of the shergottites

Abstract: sources. This suggests that the oldest group of meteorites is more closely related to one another than they are to the younger meteorites that are derived from less incompatible-element-depleted sources. Closed-system fractional crystallization of this suite of meteorites is modeled with the MELTS algorithm using the bulk composition of Yamato 980459 as a parent. These models reproduce many of the major element and mineralogical variations observed in the suite. In 2 addition, the rare-earth element systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
225
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(242 citation statements)
references
References 32 publications
15
225
1
1
Order By: Relevance
“…Fractional crystallization of primary shergottitic magma may generate major and REE variations among the older shergottites (474 Ma to 575 Ma; Dar al Gani 476, Sayh al Uhaymir 005/008, and Dhofar 019) as demonstrated by Symes et al (2008). Using the MELTS algorithm (Ghiorso and Sack, 1995), these workers found that 43% crystallization of spinel, olivine, orthopyroxene, pigeonite, clinopyroxene, and plagioclase of Y98 magma can generate compositions similar to the more evolved QUE94201.…”
Section: Rayleigh Fractional Crystallizationmentioning
confidence: 99%
“…Fractional crystallization of primary shergottitic magma may generate major and REE variations among the older shergottites (474 Ma to 575 Ma; Dar al Gani 476, Sayh al Uhaymir 005/008, and Dhofar 019) as demonstrated by Symes et al (2008). Using the MELTS algorithm (Ghiorso and Sack, 1995), these workers found that 43% crystallization of spinel, olivine, orthopyroxene, pigeonite, clinopyroxene, and plagioclase of Y98 magma can generate compositions similar to the more evolved QUE94201.…”
Section: Rayleigh Fractional Crystallizationmentioning
confidence: 99%
“…MSR (e.g. McPherson et al, 2001; Wadhwa, 2001;Borg et al, 2003;Symes et al, 2008;Shearer et al, 2008) and subsequent evolution of the crust, mantle, and core (e.g. Treiman, 1990;Shearer et al, 2008).…”
Section: Ivb Proposed Scientific Objectives For Msrmentioning
confidence: 99%
“…These mafic to ultramafic rocks provide unique samples that can be used to decipher and understand the magmatic processes and the crystallization history of Mars [5,6]. Based on the crystallization ages of SNCs (150-4500 Ma) obtained from various geochronometers such as Sm-Nd, Rb-Sr, Pb-Pb, and Ar-Ar [7][8][9][10][11][12][13][14][15][16][17], it appears that the Martian magmatism extended over most of the solar system history that agrees well with the time span of crater retention ages [18]. It is believed that shergottites-the most abundant of the Martian meteorites found to date-have been generated by the partial melting of the Martian mantle [8,19]; therefore, their geochemical signatures can provide insights into the Martian mantle chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…These meteorites are related via identical ejection ages (i.e., mean ejection age = 1.1 ± 0.2 Ma; N = 11) and compositionally identical mantle source [17]. There is no physical evidence that could suggest that these rocks are derived from the same terrain on Mars [15]. However, the majority of the depleted shergottites share similar ejection ages (1.1 ± 0.2 Ma; [17], except NWA 5990, NWA 7032, QUE 94201 (3 Ma) and Dhofar 019 (18 Ma), suggesting that most of them might have launched in a single impact probably from a similar terrain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation